The effectiveness of policies for addressing Covid-19 impacts on wildlife conservation in Vietnam - Trịnh, T. M.; Pham, T. T.; Phạm, V. T.; Cao, N. L.; Trần Ngọc, M. H. (Center for International Forestry Research, 2021)
The Covid-19 pandemic has stirred up global and national concerns over human-wildlife interactions, unsustainable and illegal wildlife trade, ecosystem degradation and the need to transform both policies and practices in achieving effective conservation outcomes. As new policies on post-Covid-19 recovery are being developed, global and national policymakers and practitioners call for scientific and rigorous assessments on the effectiveness of past and current wildlife conservation policies and projects, and the impacts Covid-19 is having on them, to provide inputs for evidencebased decision-making processes. Our paper is one of many efforts aiming to respond to this call. Based on a literature review, case study approach, and national policy dialogue, this paper aims to understand the impacts of Covid-19 on wildlife conservation, opportunities for and challenges to enhancing the effectiveness of current and future conservation schemes, and to propose recommendations for post-pandemic conservation actions.